2019
DOI: 10.1186/s13104-019-4521-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pediculosis capitis and associated factors among schoolchildren in Woreta town, northwest Ethiopia

Abstract: Objectives The aim of the study was to determine the associated risk factors and prevalence of pediculosis capitis among school-aged children in Woreta town, northwest Ethiopia. An institution-based cross-sectional study was carried out on 402 schoolchildren in Woreta town public schools from grades 1 to 4 students conducted from April to June 2018. After selection by simple random sampling, face to face interview and observations were performed using a semi-structured pre-tested questionnaire. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 19 publications
3
23
5
2
Order By: Relevance
“…In the current manuscript, we have assessed the knowledge, attitude, and practice regarding pediculus capitis prevention and control and their associated factors. Knowledge was a significant predictor of infestation status in previous studies [19,29,32]. This may be due to the lack of knowledge that can result in insufficient capacity to handle lice infestation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In the current manuscript, we have assessed the knowledge, attitude, and practice regarding pediculus capitis prevention and control and their associated factors. Knowledge was a significant predictor of infestation status in previous studies [19,29,32]. This may be due to the lack of knowledge that can result in insufficient capacity to handle lice infestation.…”
Section: Discussionmentioning
confidence: 93%
“…During the study period, there were three primary schools in the town with a total of 3239 students. The prevalence of pediculus capitis during the study period was 65.7% (95% CI 60.01-70.3%) [29]. Figure 1: Knowledge, attitude, and practice towards Pediculus capitis prevention and control among schoolchildren Woreta, 2018 (n = 402).…”
Section: Study Design Andmentioning
confidence: 99%
See 2 more Smart Citations
“…According to extensive studies, we are witnessing an increase in the prevalence of head lice in different parts of the world and Iran in recent years. It has imposed heavy financial burdens upon the health care system (9,10). Studies conducted abroad have reported the prevalence of head lice infestation in primary school students as variable, with the prevalence reported to be between 40-60% (11)(12)(13).…”
mentioning
confidence: 99%